Living Together: Representasi Atas Jalinan Persaudaraan Umat Islam Dengan Umat Antar Agama - Firdausiyah, Umi Wasilatul (Universitas Islam Negeri Raden Intan Lampung, 2021)
The discourse of this study is about Living Together Between Religious People with a discussion of the creation of brotherhood between religions and Islam as a religion of rahmatan lil alamin. This research was conducted in order to reveal the existence of togetherness between religious communities assisted by a qualitative approach with the type of library research and the analytical method using the content-analytical type, which is complemented by the sociological theory of knowledge according to Karl Manheim. The result of this study is that togetherness between religious communities in the fabric of brotherhood, both among people within religions and people between other religions, has a different concept of brotherhood, but the goal of achieving it is the same, namely to achieve a life of peace and prosperity. Although it can't be denied that conflict will always exist, minimizing it by maintaining togetherness between religious communities is a very wise choice. Then Islam as a religion that is rahmatan lil 'alamin makes brotherhood a pillar of the creation of unity and unity between religious communities, and in Islam itself, living side by side with interfaith has existed since the beginning of Islam, namely at the time of Prophet Muhammad, and continue until this day.